2015
DOI: 10.1007/s13224-015-0710-0
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Trophoblastic Neoplasia: Experience from a Tertiary Care Center of India

Abstract: Aims Gestational trophoblastic neoplasia (GTN) comprise a spectrum of interrelated conditions originating from the placenta. With sensitive assays for human chorionic gonadotropin (b-hCG) and current approaches to chemotherapy, most women with GTN can be cured with preservation of reproductive potential. The purpose of this analysis was to address the outcome of GTN in patients from a tertiary care center of India. Materials and MethodsWe undertook a retrospective and prospective review of GTN cases treated at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Several studies concluded that first pregnancies were associated with a higher risk of molar pregnancy. Riadh et al [7] reported a higher incidence of molar pregnancy in nulliparous women (28.88%), similar to the results obtained by Igwegbe et al [8,9]. Meanwhile, Anyanwu, et al [10] found a higher incidence of hydatidiform mole in multiparous women.…”
Section: K E M a L A I S N A I N I A S I H M A N T I L I D E W I E T...supporting
confidence: 67%
See 1 more Smart Citation
“…Several studies concluded that first pregnancies were associated with a higher risk of molar pregnancy. Riadh et al [7] reported a higher incidence of molar pregnancy in nulliparous women (28.88%), similar to the results obtained by Igwegbe et al [8,9]. Meanwhile, Anyanwu, et al [10] found a higher incidence of hydatidiform mole in multiparous women.…”
Section: K E M a L A I S N A I N I A S I H M A N T I L I D E W I E T...supporting
confidence: 67%
“…The mean gestational age of patients in this study was 10.79±4.646. According to Riadh et al [7] 81.24% of patients with molar pregnancies were diagnosed between 8 and 16 weeks. Gestational age is an essential parameter for diagnosing molar pregnancy due to the characteristic uterine size discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…EMACO therapy, the standard regimen for high-risk patients can lead to catastrophic hemorrhage during the first few weeks of treatment due to rapid destruction of tumor following chemotherapy. [1] In the current study, increased morbidity was noted in patients receiving upfront EMACO therapy versus initial low dose chemotherapy. Febrile neutropenia was the most common complication probably secondary to the effects of chemotherapy.…”
Section: Discussionmentioning
confidence: 54%
“…Low-dose induction EP was introduced in patients with a high burden of disease at presentation to enable a more gradual reduction in tumor bulk in the initial weeks of treatment to minimize the risk of early death. [1] Alifrangis et al conducted a retrospective study at Charring Cross Hospital, UK. [4] Between 1979 and 1995, overall survival with EMACO in high-risk GTN at their institute was 85.4%, with a significant proportion of early deaths (<4 weeks).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation